Functional dentition and prosthodontic status in an Indigenous population from the South of Brazil - Gustavo Hermes Soares; Nayara Fernanda Pereira; Adrielly Garcia Ortiz; Maria Gabriela Haye Biazevic; Edgard Michel-Crosato (Universidade Estadual de Campinas, 2019)
Aim: to analyze the prevalence of different definitions of functional dentition, prosthodontic status and associated factors, in an indigenous population from Brazil. Methods: a cross-sectional oral health survey was conducted with Indigenous adults aged 35-44 years. A single examiner collected clinical data through oral examinations and sociodemographic data using a structured questionnaire. Dentitions were classified according to four classification systems of functional dentition: FDWHO (> 20 teeth), FDGROUP2 (> 10 teeth in each arch), FDGROUP3 (all anterior teeth), and FDGROUP4 (> 10 teeth in each arch, all anterior teeth, and sufficient posterior region). Use and need of prosthodontics was also evaluated. Uni and multivariate analysis were conducted at the level of significance of 5%. Results: Indigenous adults presented considerably low frequencies of prosthodontic use and functional dentition, independently of the definition analyzed. Substantial differences of prevalence rates were observed among the four definitions of functional dentition, ranging from 48.62% to 11.93%. Age and municipality were associated with use of dental prosthesis and prosthodontic need, respectively. Significant discrepancies in functional dentition rates were observed regarding sex and time of the last dental appointment. Conclusions: Indigenous adults are severely affected by tooth loss and, consequently, by low frequencies of functional dentition. The scenario is worsened by the elevated need of the population for prosthodontics. The phenomenon was associated with age, sex, access to specialized dental care and time of the last dental visit.